Penerapan Media Papan Gulir Pintar dalam Meningkatkan Keterampilan Menulis Teks Deskripsi - Mariska, Anggi; Khaerunnisa, Khaerunnisa (BELAJAR BAHASA: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the effectiveness of using smart scroll board media in improving descriptive text writing skills in class VII.7 students of SMPN 18 South Tangerang City. The main problem faced is the low writing skills of students caused by the lack of variation in learning media and lack of motivation in writing. This study uses the Classroom Action Research (CAR) method with the Kemmis and McTaggart model which is implemented in two cycles. Each cycle consists of planning, action, observation, and reflection stages. The results of the study indicate that the use of smart scroll board media can increase student motivation and participation in writing activities. Quantitatively, there was an increase in the average value of writing skills from 64 in the pre-cycle stage to 78 in cycle I, and increased further to 90 in cycle II. In addition, students showed better creativity in composing descriptive texts, with the use of more varied diction and clearer sentence structures. Feedback from teachers and students also showed that this media was effective in improving the quality of learning.